Clinical trial of gabexate in the prophylaxis of post-endoscopic retrograde cholangiopancreatography pancreatitis - Xiong,G.-S. (2006)
The objective of the present study was to determine the efficacy of prophylactic administration of gabexate for the prevention of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis, hyperamylasemia and pancreatic pain. Patients scheduled for ERCP were randomized into two groups in a double-blind manner: the patients in the gabexate group were treated with continuous intravenous infusion of 300 mg gabexate dissolved in 500 mL Ringer's solution at 111 mL/h, starting 30 min before the endoscopic maneuvers and continuing up to 4 h after them; placebo group patients were treated only with Ringer's solution also starting 30 min before the endoscopic maneuvers and continuing up to 4 h. Data for 193 patients were analyzed. The incidence of post-ERCP pancreatitis was 3 patients (3.1%) in the gabexate group and 10 (10.5%) in the placebo group (P = 0.040). The incidence of hyperamylasemia was 33 patients (33.7%) in the gabexate group and 42 (43.7%) in the placebo group (P = 0.133). The incidence of pancreatic pain was 15 patients (15.3%) in the gabexate group and 28 (29.5%) in the placebo group (P = 0.018). The results suggest that a 4.5-h infusion of gabexate (for a total of 300 mg) could prevent post-ERCP pancreatitis and pancreatic pain.